The The Effect of Outdoor Activity Method on Learning Activity and Science Learning Outcomes - Alfrida Yani Pabete; Mas’ud Badolo; Rifat Shafwatul Anam (PT ARRUS Intelektual Indonesia, 2023)
The aims of this research was to analyze effect of learning using the outdoor activity method on students' science learning activities and outcomes in the matter of energy and its changes. This learning experiment has a one group pretest-posttest design through a quantitative approach using statistical data analysis obtained from 21 fourth grade students at SDN 18 Sadan who were sampled. Data was collected using tests for student learning outcomes, while student activity during learning was measured using questionnaires and observations. Based on the numbers obtained, the average score of student learning activities is 45.05 and is in the high category. Based on observations obtained in general 85.5% are active when learning. Based on the analysis of learning outcomes data with the t test, the sig value was obtained. 0.000 which leads to the conclusion that the outdoor activity method has an influence on the activities and learning outcomes of science students in class IV SD Negeri 18 Sadan.